2021
DOI: 10.1002/eco.2319
|View full text |Cite
|
Sign up to set email alerts
|

Water depth influences algal distribution and productivity in shallow agricultural lakes

Abstract: Agricultural activity can alter water quality and quantity resulting in lakes facing increasing interactive stressors including eutrophication, suspended sediment and water withdrawal. This study examined the relationships between water depth, water quality and algae in shallow agricultural lakes in the lower Mississippi River Basin (LMRB) to assess how lake depth influences algal structure and function, focusing on factors that typically regulate growth, that is, light, temperature and nutrients. Lake water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…A previous study showed that the total soluble protein (TSP) content decreased while the growth rate increased with increasing light intensity and sunlight duration [ 16 ]. The relative photosynthetic response of the alga varies with regional climate and aquatic physicochemistry [ 17 ]. Observed differences in P. dentata photosynthesis are associated with biotic and abiotic stressors, including temperature extremes, ocean acidification, carbon fixation rates, tides, salinity level [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that the total soluble protein (TSP) content decreased while the growth rate increased with increasing light intensity and sunlight duration [ 16 ]. The relative photosynthetic response of the alga varies with regional climate and aquatic physicochemistry [ 17 ]. Observed differences in P. dentata photosynthesis are associated with biotic and abiotic stressors, including temperature extremes, ocean acidification, carbon fixation rates, tides, salinity level [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, changes in wind direction are a significant factor influencing lake hydrodynamics [195]. The distribution of algal blooms with lower nutrient concentrations is influenced by water depth, water temperature and turbidity [196]. The result observation from Mei et al revealed that the temperature difference with 1.7 % average higher increased the nutrient concentrations [197].…”
Section: B Hydromorphological Elementsmentioning
confidence: 99%
“…In addition, hydrologic variables such as lake depth and lake area revealed that lakes trending eutrophic tended to be smaller and shallower than other lakes. Small, shallow lakes are often more productive than deeper lakes because of the effects that lake morphology can have on ecosystem structure (Richardson et al, 2022;Henderson et al, 2021).…”
Section: Productivity Trendsmentioning
confidence: 99%